Delayed cerebellar ataxia: A rare self limiting complication of plasmodium falciparum malaria - Sakaria, Amit K. (Medknow Publications & Media Pvt Ltd, 2013)
The classic presentation of malaria with paroxysms of fever is seen only in 50-70% of the patients. The development of immunity, the increasing resistance to anti-malarial drugs, and the indiscriminate use of anti-malarial drugs have led to malaria with the presentation of unusual features. Cerebellar ataxia, extrapyramidal rigidity and various psychiatric symptoms have been described either as early manifestations of cerebral malaria or as a part of post malaria neurological syndrome. In this case report, we will discuss one such patient of falciparum malaria infection who developed midline cerebellar signs, and responded to anti-malarial treatment.